The measurement of the vertical relief on metal-graphic microscopes of production of OJC «Optoelectronic systems» - A. G. Anisovich; A. S. Buinitskaya (Литьë и металлургия, 2019)
The possibilities of measuring the depth of the surface relief on metallographic microscopes manufactured by OJSC «Optoelectronic systems» are illustrated. For the microscopes MI-1 and MICRO-200 a technique for determining the height of the relief is considered, which is based on the relationship between the angle of rotation of the drum tincture of precise focus and vertical movement of the object table. Examples of crater depth measurements after exposure to laser radiation on a metal surface are given. For MI-1 and MICRO-200 microscopes, the depth of the well was determined as 99.36 and 99.8 µm, respectively, which is consistent with the profilometer data (~100 µm). For a plane-parallel quartz plate, the measurement results were 0.435 µm when determined microscopically, as well as the object-micrometer. The possibility of determining the thickness of titanium nitride coatings by differential interference contrast is considered. The method allows the determination of the thickness of the difference in interference colors, if the image areas are at different heights. The thickness of the coating can be estimated using a nomogram of double refraction.